Pengembangan Sistem Informasi Pendaftaran Praktek Kerja Lapangan (PKL) dengan Konsep Hierarchical Model View Controller (HMVC) - Suci Nurfauziah; Tri Ramadani Arjo (Journal of Applied Informatics and Computing, 2021)
Registration for Praktek Kerja Lapangan (PKL) in the Administration Business department has not been maximized. Some of the problems that occur include student registration which is still semi-manual so that it prolongs the registration process, one company only have three students for each Study Program so that students have to fight, this makes it difficult for the admin, manual PKL registration makes students have to queue in the administration room. The development of an information system with the HMVC pattern is able to make easier for programmers. Programmer can divide the system into more specific modules so that the execution of applications is more flexible. This research purpose to develop a registration information system for Praktek Kerja Lapangan (PKL) by applying the HMVC (Hierarchical Model View Controller) concept. The test results of the three experts show that all features of the PKL registration information system are running and functioning properly. And then, stress testing with Jmeter also showed satisfactory results, using 42 users / samples the average response time was less than 5 seconds and there were no errors.